2001
DOI: 10.1007/s002510100361
|View full text |Cite
|
Sign up to set email alerts
|

The major histocompatibility complex of the rat (Rattus norvegicus)

Abstract: This review of the RT1 complex, the major histocompatibility complex (MHC) of the rat, focuses on genetic, genomic, evolutionary, and functional aspects at the molecular level. The class I, class II, and framework genes are listed. The physical map of the RT1 complex as revealed by analysis of clonal contigs is compared with the human and mouse MHC, and the degree of orthologous relationship is outlined. Elucidation of the RT1 complex provides important information for using the rat as a model of experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 169 publications
1
87
0
1
Order By: Relevance
“…6, A and B). LEW and F344 rats are genetically identical in RT1.A and RT1.B/D (classical class I and class II MHC) genes, but differ in RT1.C/E/M regions of the rat MHC (41,42). If Ly-49G BALB/c recognizes a rat MHC ligand, then a nonclassical molecule encoded in the RT1.C/ E/M region of the RT1 1 haplotype may be a ligand.…”
Section: Discussionmentioning
confidence: 99%
“…6, A and B). LEW and F344 rats are genetically identical in RT1.A and RT1.B/D (classical class I and class II MHC) genes, but differ in RT1.C/E/M regions of the rat MHC (41,42). If Ly-49G BALB/c recognizes a rat MHC ligand, then a nonclassical molecule encoded in the RT1.C/ E/M region of the RT1 1 haplotype may be a ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic architecture of the MHC has been detailed for several model vertebrate species, most notably in humans (termed HLA; MHC Sequencing Consortium, 1999), mouse (H-2; Younger et al, 2000), rat (RT-1; Gunther and Walter, 2001;Hurt et al, 2004) and chicken (B-locus; Kaufman et al, 1999). There are similarities across these model systems in MHC structure, in that the class I and class II genes are linked together in a single gene complex in each case (Hughes and Yeager, 1998;Hess and Edwards, 2002).…”
Section: The Structure and Function Of The Mhcmentioning
confidence: 99%
“…The better purified myoblasts led to an augmentation of transplantation efficiency (Qu and Huard 2000). Günther and Walter (2001) found that highly purified MDSCs expressing both type I and type II major histocompatibility complex could completely avoid rapid cell death after transplantation, indicating that purification of MDSCs can prevent immune rejection. The proportion of MDSCs in skeletal muscle cells is low, approximately 1-5 % (Kuang et al 2007).…”
Section: Introductionmentioning
confidence: 99%